Is Lithuanian a polysynthetic language? - Arkadiev, Peter (Vilnius University Open Series, 2021)
This paper reviews the definitions and operationalisations of the notion of “polysynthesis” proposed in the typological literature and applies them to Lithuanian (verbal) morphology. It is shown that while Lithuanian falls short of polysynthesis in terms of morphemes-to-words ratio and lacks such features as polypersonalism and incorporation, it still possesses certain properties associated with polysynthesis. These include the so-called lexical affixes (it is argued that Lithuanian verbal prefixes are an example of these) and, to a limited extent, “productive non-inflectional concatenation”, i.e. morphemes with a high combinatory potential and compositional meanings, including successively applying verbalisers and nominalisers. These observations not only shed novel light on some well-known facts of Lithuanian grammar, but also further underscore the multifactorial and vague nature of polysynthesis.
Keywords: Lithuanian; morphology; polysynthesis; typology; verb